PATIENT'S RIGHT TO FAIR AND NON-DISCRIMINATORY TREATMENT: LEGAL AND ETHICAL PERSPECTIVES - Gunawan Widjaja; Dyah Ersita Yustanti; Hotmaria Hertawaty Sijabat; Handojo Dhanudibroto (CV. Adiba Aisha Amira, 2025)
The patient's right to fair and non-discriminatory treatment is an important part of the fulfilment of human rights in the health sector. This study examines legal protection and the application of ethics in guaranteeing this right, by reviewing various laws and regulations such as Law Number 36 of 2009 concerning Health and Law Number 44 of 2009 concerning Hospitals, as well as the principles of medical ethics. The results of the study show that patient rights include the right to clear information, quality medical services, privacy, and access to complaints in the event of a violation. However, implementation in the field still faces challenges, especially in the form of discrimination against certain groups such as BPJS patients. Therefore, synergy between legal protection, ethical implementation, supervision, and patient education is needed so that the right to fair treatment and without discrimination is truly realised in health care practices.